Unlocking the Medinan Qurʼan - Sinai, Nicolai 1976- (Brill, 2022)
Introduction / Nicolai Sinai -- Part I. Literary Features of the Medinan Qurʼan: 1. Towards a Compositional Grammar of the Medinan Suras / Nicolai Sinai -- 2. Lexical Layers vs. Structural Paradigms in the Opening of Sūrat alBaqara: Typically Medinan Structures in Q 2, Q 3, and Some Shorter Medinan Compositions / Marianna Klar -- 3. Formulae and Repetition in the Medinan Qurʼan: The Story of the Golden Calf between Meccan and Medinan Suras / Cecilia Palombo -- 4. Interrogative Rhetoric and Deliberative Discourse in the Medinan Suras / Nora K. Schmid -- 5. Vocatives in the Qurʼan and the Framing of Prophetic Proclamations / Devin J. Stewart -- Part II. Ritual, Prophetology, and Law: Some Medinan Themes: 6. The Qibla of Muhammad's Community Reconsidered / Angelika Neuwirth -- 7. Obeying God and His Messenger: Medinan Prophetology in the Meccan Qurʼan? / Andrew J. O'Connor -- 8. Law in the Medinan Qurʼan: The Case of Biblical Incest Law and Its Qurʼanic Reiteration / Holger Zellentin -- Part III. Studies of Individual Suras: 9. The Dynamics of Sūrat Āl ʻImrān (Q 3) / Neal Robinson -- 10. A Guide to the Legal Material in Sūrat al-Nisāʼ (Q 4) / Joseph E. Lowry -- 11. Emotive Rhetoric, Plot, and Persuasion in a Jihād Surah (Q 8 al-Anfāl) / Karen Bauer -- 12. Intratextuality, Doublets, and Orality in the Qurʼan, with Attention to Suras 61 and 66 / Gabriel S. Reynolds --13. Q 63 (Sūrat al-Munāfiqūn): A Text-Critical and Structural Analysis / Saqib Hussain -- Index
Includes bibliographical references and index
2204
Keywords: Koran; Geschichte; Islam; Qurʼan / History of Qurʼanic events; Qurʼan / Criticism, Textual; Qurʼan / Criticism, interpretation, etc; Qurʼan / History; Aufsatzsammlung